WORKSHOP KREASI MEDIA PIPE CLEANER DALAM MENGEMBANGKAN KETERAMPILAN MOTORIK HALUS ANAK USIA DINI BAGI GURU PAUD DI RA ABATA MARDHOTILLAH KABUPATEN KARAWANG - Siti Aisyah, Dewi; Trina Rahayu, Ega; Ulya, Neng; Aisyah, Dinda (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Pipe cleaner media creation training on fine motor skills of early childhood is the creation of media according to early childhood development aspects in the form of handicrafts and various games with pipe cleaner media. The novelty of this pipe cleaner media is one of the most popular craft materials. easy to form and create and its flexible nature makes it easier for children to be creative and can train children's fine motor skills. The existence of this PKM program aims to assist teachers in making APE or learning media in improving children's fine motor skills. This PKM activity has been successfully held twice, the first online to introduce pipe cleaner media on November 19, 2021 with a total of 130 participants consisting of PAUD teachers in the Karawang district and the second offline for training on making pipe cleaner media creations. for teachers RA Abata Mardhotilla karawang district.